Epistemic Modality in Travel Blogs - Zmrzlá, Karolína (Univerzita Pardubice, 2025)
This bachelor thesis deals with English modal verbs expressing possibility and uncertainty in travel blog discourse. The thesis presents modality with its three main types together with modal verbs that are analysed later. Modal verbs expressing epistemic possibility and the speaker's uncertainty are the main focus of the thesis. Furthermore, the travel blog discourse is introduced. The analysis of articles collected from various travel blogs focuses on describing contexts in which modal verbs occur with regard to the function of the travel blog discourse.
Epistemická modalita v cestovatelských blozích
Keywords: modalita; epistemická modalita; modální slovesa; diskurz cestovatelských blogů; možnost; jistota; may; might; can; could; modality; epistemic modality; modal verbs; travel blog discourse; possibility; certainty; may; might; can; could